2015
DOI: 10.1186/s12871-015-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal effect of remifentanil in general anaesthesia for caesarean section: a randomized trial

Abstract: BackgroundRemifentanil has been suggested for its short duration of action to replace standard opioids for induction of general anaesthesia in caesarean section. While the stabilizing effect of remifentanil on maternal circulation has been confirmed, its effect on postnatal adaptation remains unclear, as currently published studies are not powered sufficiently to detect any clinical effect of remifentanil on the newborn.MethodsUsing a double-blinded randomized design, a total of 151 parturients undergoing caes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 27 publications
(26 reference statements)
1
45
3
4
Order By: Relevance
“…Noskova et al [17] reported that a bolus of 1 μg/kg remifentanil before induction of general anesthesia decreased Apgar scores at 1 min after cesarean delivery, although the clinical symptoms were short. These observations were not found in the current study, because the dosage of remifentanil injection was lower than in the prior studies [17,18] .In this study, four neonates were needed resuscitation. In parturients with remifentanil, the reasons of resuscitation were umbilical cord around neck and the long delivery time of the fetus (from skin cutting to fetal delivery).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Noskova et al [17] reported that a bolus of 1 μg/kg remifentanil before induction of general anesthesia decreased Apgar scores at 1 min after cesarean delivery, although the clinical symptoms were short. These observations were not found in the current study, because the dosage of remifentanil injection was lower than in the prior studies [17,18] .In this study, four neonates were needed resuscitation. In parturients with remifentanil, the reasons of resuscitation were umbilical cord around neck and the long delivery time of the fetus (from skin cutting to fetal delivery).…”
Section: Discussioncontrasting
confidence: 80%
“…Many studies have shown that remifentanil (an off label drug for parturient) has less adverse neonatal or maternal effects during cesarean section; thus, they have suggested its use as a replacement for standard opioids in cesarean section [8][9][10] . In our clinic, we found that continuous intravenous infusion of low-dose remifentanil has a good rescue analgesic effect on incomplete epidural analgesia and provides a degree of sedation during cesarean section, which improves the patient experience.…”
Section: Introductionmentioning
confidence: 99%
“…Zur Sectio caesarea wurde eine erhöhte Inzidenz für eine neonatale Atemdepression festgestellt, wenn Remifentanil (1 µg/kg) vor Beginn der Operation appliziert wurde [17]. Eine Metaanalyse von 5 Publikationen kam zu dem Schluss, dass anhand der vorliegenden Daten und der Power der Studien keine gültige Aussage zur Sicherheit von Remifentanil zur anästhesiologischen Einleitung einer Sectio caesarea getroffen werden kann [18].…”
Section: Einsatz Bei Schwangerenunclassified
“…Therefore, the precise control of stress replication is necessary during the inspiration of anesthesia in preeclamptic patients. Various pharmacologic attempts have so far been made to suppress these pressor responses like opioids, lidocaine, along with α and β adrenergic blockers (8)(9)(10)(11)(12)(13)(14). Remifentanil is shown to attenuate hemodynamic replication to intubation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is ultra-short acting opioid and very metabolized by placenta esterase, thus the fetal to maternal ratio is low. It has a short onset and rapid recovery time as well (1,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Similarly, labetalol is an α and (β 1 & β 2 ) adrenergic receptor blocker and competes with the other catecholamine for binding these sites, therefore, it can suppress increased blood pressure (BP) and heart rate owing to the activation of the sympathetic nervous system during the intubation (9,16).…”
Section: Introductionmentioning
confidence: 99%